Valuing Improvements in The Water Rights System in South Africa: A Contingent Ranking Approach1 - (:unkn) unknown (My University, 2010)
In the context of increasing water scarcity, understanding is growing that irrigation water rights are important and that a lack of an effective water rights system constitutes a major reason for inefficient water management. This study carried out a contingent ranking experiment to study how smallholder irrigators in South Africa would value potential changes in water rights. Three specific dimensions of water rights, relevant for the South African case, are considered: duration, quality of title, and transferability. Results indicate that smallholder irrigators are prepared to pay considerably higher water prices if improvements are made in the water rights system. This implies that the proposed interventions in the water rights system would improve the efficiency and productivity of the small-scale irrigation sector. The increased willingness to pay could furthermore also assist the South African government to reach the objective of increased cost recovery.
Keywords: African Research